EFEKTIVITAS WILLIAM’S FLEXION EXERCISE DALAM PENGURANGAN NYERI HAID (DISMENORHEA) - Oktaviani, Anisa Sevi; Lestari, Uti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Menstrual pain (dysmenorrhea) is pain that occurs before or during menstruation. In Indonesia, the incidence of dysmenorrhea is 64.25%, which comprises 54.89% of primary menstrual dismenorhea and 9.36% of menstrual pain (dysmenorrhoea) secondary. Of this study will provide a simple and easy preventive therapy alternative to reduce menstrual pain (dysmenorrhea). The purpose of the study was to determine the effectiveness of william's flexion exercise in reducing menstrual pain (dysmenorrhea) at Midwifery Academy Graha Mandiri Cilacap. Types of Research: This type of research uses pre-experimental design research design with pretest-posttest design. The population is Akbid Graha Mandiri Cilacap as much as 35 students, and the sample is 26 female students. The sampling technique is purposive sampling. Data analysis technique used wilcoxon matched pairs test with SPSS 16 program. The conclusion of william's flexion exercise is effective in reducing menstrual pain (dismenorhea) at Midwifery Academy Graha Mandiri Cilacap. Keywords : Menstrual pain, dysmenorrhea, william's flexion exercise